Multiply the radicals: (x^3 y)^1/4 * (x^2 y^2)^1/3

Please show solution with everything in its simplest form.

### 1 Answer | Add Yours

The product `(x^3y)^(1/4)*(x^2 y^2)^(1/3)` has to be determined

`(x^3 y)^(1/4) * (x^2 y^2)^(1/3)`

=>`x^(3/4)*x^(2/3)*y^(1/4)*y^(2/3)`

=> `x^(3/4 + 2/3)*y^(1/4 +2/3)`

=> `x^(17/12)*y^(11/12)`

**The product of **`(x^3y)^(1/4) * (x^2 y^2)^(1/3) = x^(17/12)*y^(11/12)`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes